A telemedicine intervention to improve adherence to continuous positive airway pressure: a randomised controlled trial. Issue 12 (29th September 2010) - Sparrow, David; Aloia, Mark; DeMolles, Deborah A; Gottlieb, Daniel J
Abstract : Background: Continuous positive airway pressure (CPAP) is the most widely prescribed treatment for obstructive sleep apnoea syndrome (OSAS). Although it has been shown to improve the symptoms of OSAS, many patients have difficulty adhering to this treatment. The purpose of this study was to investigate the effectiveness of an automated telemedicine intervention to improve adherence to CPAP. Methods: A randomised clinical trial was undertaken in 250 patients being started on CPAP therapy for OSAS. Patients were randomly assigned to use a theory-driven interactive voice response system designed to improve CPAP adherence (telephone-linked communications for CPAP (TLC-CPAP), n=124) or to an attention placebo control (n=126) for 12 months. TLC-CPAP monitors patients' self-reported behaviour and CPAP-related symptoms and provides feedback and counselling through a structured dialogue to enhance motivation to use CPAP. A Sleep Symptoms Checklist, the Functional Outcomes of Sleep Questionnaire, the Center for Epidemiological Studies Depression Scale and the Psychomotor Vigilance Task were administered at study entry and at 6-month and 12-month follow-up. Hours of CPAP usage at effective mask pressure were measured by the CPAP device stored in its memory and retrieved at each visit. Results: Median observed CPAP use in patients randomised to TLC-CPAP was approximately 1 h/night higher than in the control subjects at 6 months and 2 h/night higher at 12 months. Using generalised estimating equation modelling, the intervention had a significant effect on CPAP adherence. For secondary analysis, the effect of CPAP adherence on the secondary outcomes was analysed. CPAP adherence was significantly associated with a greater reduction in sleep apnoea symptoms and depressive symptoms and a greater improvement in functional status. No significant association was observed between CPAP adherence and reaction time. Conclusions: The TLC-CPAP intervention resulted in improved CPAP adherence, which was associated with improved functional status and fewer depressive symptoms. Clinical trial.gov: NCT00232544.